Isyatur Radhiyah PEMEROLEHAN KALIMAT BAHASA INDONESIA ANAK USIA DINI - isyatur radhiyah (Darul Ulum: Jurnal Ilmiah Keagamaan, Pendidikan dan Kemasyarakatan, 2020)
The development of the child language is begin from born to the age of 5 years has in particular gained thousands of vocabulary, phonological and grammatical systems and the same complex rules for using their language appropriately in many social background. Acquisition is a process of mastery of language done by children naturally when he learned the first language or his mother tongue. In this case, there are two processes that occur in it, namely the acquisition of language and language learning. Based on that statement, this study aims to describe the acquisition of Indonesian, especially the acquisition phrases and senteces of Indonesian children early age four to five years old. This research uses a qualitative approach with descriptive research type of analysis. The center of this research is the acquisition of Indonesian sentence children of early as a source of data. Techniques refer libat proficient, recording techniques, and note taking techniques is a technique used by author to collect data in this study. The results of this study found variations of phrases and sentences. The phrase in question is a phrase consisting of a nominal phrase, a verbal phrase, a numeral phrase, an adverbial phrase, a preposition phrase, and an adjective phrase. In addition to acquiring phrases, early childhood also acquires sentences consisting of core sentences and non-core sentences, single sentences and compound sentences, major sentences and minor sentences, verbal sentences and non-verbal sentences, as well as free sentences and bound sentences. Thus, the results of this study can be used as one of the comparative materials with subsequent studies that will examine research on the acquisition of Indonesian sentences for early childhood, although the aspects studied are different. Key words: earnings, sentences, early childhood